Changing of cytokine status in acute period of tick-borne neuroinfections in children - T. Yu. Bedareva; T. V. Poponnikova; G. Yu. Galiyeva; O. S. Pinevich; T. N. Vakhrameyeva (Бюллетень сибирской медицины, 2009)
Activity of cytokines of tick-borne infection of children was researched. Revealed low level of interferon-γ concentration testify about abnormality of cellular link immune protection and typical for focal forms of tick-borne encephalitis. Severe forms of disease run with background increase of interleukin-6 and interleukin10. Maximum increase of tumor necrosis factor-α was detected in cases of mixed-infections. Borreliosis infection flows with background domination of Th-2 over Th-1 type of immune response.